Climate change and corporate creditworthiness: International evidence - Nguyen H; Pham AV; Pham MDM; Pham MH (Elsevier Inc, 2025)
This study examines how climate change risks affect corporate credit ratings worldwide. Using a comprehensive dataset of 4427 firms across 60 countries, we find that firms in countries more susceptible to climate change receive lower credit ratings. Such a negative relation ensues from inferior firm fundamentals, such as higher default risk and cash flow volatility associated with climate-change-related uncertainties. We also find that the adverse impact of climate change risks on credit ratings impedes firms' access to debt financing and increases the costs of holding credit default swaps. Further analyses reveal that institutional factors and market attention to climate change significantly shape rating agencies' responses to climate change risks.
Keywords: Climate change risk; Credit ratings; Debt market; Corporate default